Multi-stimuli-responsive and dynamic color tunable security ink for multilevel anticounterfeiting - Dubey C.; Yadav A.; Baloni D.; Singh S.; Singh A.K.; Singh S.K.; Singh A.K. (My University, 2025)
Luminescent security features have been used for anticounterfeiting for a long time. However, constant effort is required to strengthen these security features to be ahead of counterfeiters. Here, we developed a multi-stimuli-responsive luminescent security ink containing Tb(ASA)3Phen, K2SiF6:Mn4+, and NaYF4:Yb3+/Er3+ luminescent materials in PVC gold medium. Tb(ASA)3Phen complex shows a broad excitation band in the UV region; upon UV light radiation it shows strong greenish emission of Tb3+ ions through the antenna effect. K2SiF6:Mn4+, on the other hand, has three excitation bands with maxima at 248, 354, and 454 nm which emit red light after excitation through these bands. NaYF4:Yb3+/Er3+ is used as an upconverting nanophosphor showing green emission under 976 nm laser excitation. Thus, the multi-stimuli-responsive luminescent security ink shows greenish, red, and green emissions under 367 nm, 450 nm, and 976 nm excitations, respectively. Furthermore, the distinct lifetimes of the activators in Tb(ASA)3Phen and K2SiF6:Mn4+, i.e. 0.1708 ms and 8.165 ms, respectively, under 380 nm excitation make this ink suitable for dynamic anticounterfeiting as well. The ink shows a change in the emission color with time delay, after the removal of the 380 nm excitation source, from greenish yellow (at 0 delays) to reddish color after a delay of 7.5 ms. These unique optical features along with excellent photo-, chemical- and environmental stability make this ink useful for advanced-level anticounterfeiting. © 2023 IOP Publishing Ltd.